(181) محاضرات في علم المالية العامة Lectures in Public Finance - عاطف السيد (معهد التخطيط القومي, 2026)
تتناول المذكرة محاضرات في علم المالية العامة الجزء الاول وفيها تتعرض للمبادر الأساسية لعلم المالية والنفقات العامة بتعريفها وانواعها وتقسيمتها وكذلك التقسيمات التحليلية للنفقات العامة من خلال فصلين، ويتناول الفصل الثالث فيها العلاقة بين الهيكل الاقتصادي للدولة ونفقاتها العامة في حين يتناول الفصل الرابع النفقات العامة في الجمهورية العربية المتحدة ومن خلال من خلال هذه المحاضرة يحاول الكاتب تحديد معنى النفقات العامة وعناصرها اي الشروط اللازمة التي حتى تعتبر نفقات عامه والتغلغل داخل هذه النفقات لتقسيمها حسب طبيعتها تارة وحسب جهة الانفاق تارة اخرى بهدف اعطاء فكره عامه عن انواع النفقات المختلفة التي تتضمنها ميزانيات مختلف الدول وكذلك بيان اذا كان هناك علاقه بين النفقات العامة ومستوى الدخل القومي او مستوى مجمل الانتاج القومي وينتهي البحث بدراسة مقتضبه عن النفقات العامة في الجمهورية العربية المتحدة تخلص الى انه النفقات العامة التي تقوم بها الدولة يجب ان تتصور في مقابلها ايرادات عامة تحصل عليها الدولة لتغطي بها هذه النفقات كما كذلك ضرورة تصور مصادر لهذه الايرادات اي موارد عامة تلجا اليها الدولة للحصول على الايرادات وتشير الدراسة الى ان الجزء الثاني من منها سيتناول الموارد العامة This memorandum comprises lectures on public finance, Part One, which covers the fundamental principles of public finance and public expenditures, defining them, outlining their types and classifications, and providing analytical classifications of public expenditures across two chapters. The third chapter examines the relationship between the state's economic structure and its public expenditures, while the fourth chapter focuses on public expenditures in the United Arab Republic. Through this lecture, the author attempts to define the meaning of public expenditures and their components—that is, the necessary conditions for something to be considered public expenditure. The memorandum delves into these expenditures, classifying them according to their nature and, at other times, according to the spending entity. The aim is to provide a general overview of the different types of expenditures included in the budgets of various countries, as well as to determine whether there is a relationship between public expenditures and the level of national income or the level of gross national product. The research concludes with a brief study of public expenditures in the United Arab Republic, which asserts that public expenditures undertaken by the state must be matched by corresponding public revenues that the state receives to cover these expenditures. It also emphasizes the necessity of identifying the sources of these revenues—that is, the public resources that the state resorts to in order to obtain them. The study indicates that the second part will address public resources.